Analysis Of Factors Influencing The Adoption Of Sharia-Based Non-Cash Payments In Medan City - Abdul Hadi Ismail; Asmawarna Sinaga; Sariyanto Sariyanto (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study aims to analyze the influence of technology, trust and risk, and Sharia compliance on the adoption of Sharia-based cashless payment systems among the people of Medan City. A quantitative approach was employed using a survey method through questionnaires distributed to respondents who were familiar with or had experience using Sharia-based cashless payment services. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that technology has a significant effect on the adoption of Sharia-based cashless payments, with a p-value of 0.027. Meanwhile, trust and risk (p-value = 0.462) and Sharia compliance (p-value = 0.166) do not have a significant effect on adoption. The R-Square value of 0.143 indicates that the independent variables explain 14.3% of the variance in Sharia-based cashless payment adoption, while the remaining variance is influenced by other factors outside the research model. These findings suggest that technology is the primary factor influencing users’ decisions to adopt Sharia-based digital payment services. The study provides practical insights for Islamic banks, digital payment providers, and regulators in developing a more effective, inclusive, and sustainable Islamic digital payment ecosystem.